Immateriell Kapital 2017
DOI: 10.18261/9788215028163-2017-03
|View full text |Cite
|
Sign up to set email alerts
|

Kapittel 3: Nye sentrum–periferi-mønster

Abstract: Kapittel 3Nye sentrum-periferi-mønster? Tilgang til kompetanse gjennom arbeidsinnvandring FINN OVE BÅTEVIK OG GRO MARIT GRIMSRUD SAMANDRAG Innvandringa til Vestlandet er sterkt prega av arbeidsinnvandring. Ved hjelp av registerdata gir dette kapitlet innsikt i korleis denne innvandringa påverkar busetnadsmønster og tilgang på arbeidskraft i landsdelen. Temaet blir drøfta ut frå det vi kallar ein utarmingsmodell og ein utjamningsmodell. Desse modellane blir vidare plasserte i eit sentrum-periferi-perspektiv. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Although the majority of EU11 labour migrants work in manual and low-skilled jobs (Friberg 2016), not all of them do. In a study of the regions of western Norway, Båtevik and Grimsrud (2017) found that the peripheral regions receive relatively more high-competence workers, such as those in the academic professions, through international labour migration than the central regions do, thus reducing the traditional 'peripheral disadvantages.' They also, however, note that there are big differences among the peripheral regions.…”
Section: International Labour Migration As Demographic Refill and Expmentioning
confidence: 99%
“…Although the majority of EU11 labour migrants work in manual and low-skilled jobs (Friberg 2016), not all of them do. In a study of the regions of western Norway, Båtevik and Grimsrud (2017) found that the peripheral regions receive relatively more high-competence workers, such as those in the academic professions, through international labour migration than the central regions do, thus reducing the traditional 'peripheral disadvantages.' They also, however, note that there are big differences among the peripheral regions.…”
Section: International Labour Migration As Demographic Refill and Expmentioning
confidence: 99%